A clinicopathological study of ALS with L126S mutation in the SOD1 gene presenting with isolated inferior olivary hypertrophy. Issue 2 (20th December 2019) - Hideshima, Makoto; Beck, Goichi; Yamadera, Misaki; Motoyama, Yuichi; Ikenaka, Kensuke; Kakuda, Keita; Tsuda, Hiroshi; Nagano, Seiichi; Fujimura, Harutoshi; Morii, Eiichi; Murayama, Shigeo; Mochizuki, Hideki
Abstract : We report an autopsy case of amyotrophic lateral sclerosis with L126S mutation in the superoxide dismutase 1 (SOD1) gene ( SOD1 ). The patient was a 69‐year‐old Japanese man without relevant family history, who initially presented with slow progressive muscle weakness of the lower extremities without upper motor neuron signs, and died of respiratory failure 6 years after the onset. Neuropathological examination revealed a loss of lower motor neurons and degeneration of Clarke's column commensurate with that of the posterior spinocerebellar tract and the middle root zone of the posterior column. The primary motor area was minimally affected. Characteristic SOD1‐immunopositive neuronal intracytoplasmic inclusions, mixed with neurofilament accumulation, were present in the affected areas. Isolated inferior olivary hypertrophy was observed, but did not involve the contralateral dentate nucleus, or the ipsilateral red nucleus and central tegmental tract, where no neuronal inclusions were found. In combination with data from a previous autopsy case, this study suggests that the L126S mutation may cause focal neuronal degeneration in the brainstem.